СУЧАСНІ ПРОБЛЕМИ ТА ПРІОРИТЕТНІ НАПРЯМКИ ФОРМУВАННЯ ВИДАТКІВ МІСЦЕВИХ БЮДЖЕТІВ - Михайленко, Світлана Володимирівна; Зубріліна, Валерія Володимирівна (Науковий журнал «Світ фінансів», 2017)
Михайленко С. В., Зубріліна В. В. Сучасні проблеми та перспективні напрямки формування видатків місцевих бюджетів. Проведено узагальнення теоретичних поглядів науковців щодо трактування змісту поняття “видатки місцевих бюджетів”. Проаналізовано структуру видатків місцевих бюджетів України, зокрема Одеської області. Визначено основні проблемні питання у розмежуванні функціональних повноважень між центральною владою та органами місцевого самоврядування. Михайленко С. В., Зубрилина В. В. Современные проблемы и приоритетные направления формирования расходов местных бюджетов. Обобщены теоретические взгляды ученых относительно содержания понятия “расходы местных бюджетов”. Проанализирована структура расходов местных бюджетов Украины, в частности Одесской области. Определены основные проблемные вопросы в разграничении функциональных полномочий между центральной властью и органами местного самоуправления. Mykhailenko S., Zubrilina V. Modern problems and priorities for the formation of expenditures of local budgets. Introduction. In the process of budget reform in Ukraine importance to the issues of formation of expenditures of local budgets because they play an important role in the economic growth of administrative groupings, reflect the priorities of social development, providing a decent level of welfare of citizens. Existing approaches to the formation of local budgets do not create conditions for effective and responsible implementation by local authorities of their functional responsibilities as legislation Ukraine does not contain a clear division of responsibilities between the central government and local government, does not clearly define the responsibility for decision-making and the provision of specific types of public goods and services not interest the local authorities to find additional sources to increase their own revenue base. The above problems caused the need to understand the formation of local expenditures and determine priorities reform process. The purpose of the article is to identify and substantiate the main problems in the formation of the expenditure part of local budgets and determining ways to address them.Results. A generalization of the theoretical views of the scientists to the interpretation of the concept of “costs of local budgets.” The structure of local budget expenditures in Ukraine and the Odessa region, which allowed to establish peculiarities of the expenditure part of local budgets. The main problematic issues in the delineation of the functional powers between central government and local authorities. The measures of organizational and legal nature, which should contribute to the implementation of the principles in the Ukrainian practice of budget decentralization.